Peru : The World Bank Group Country Opinion Survey FY 2014 - World Bank Group (World Bank, Washington, DC, 2015)
The Country Opinion Survey in Peru assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Peru perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Peru on 1) their views regarding the general environment in Peru; 2) their overall attitudes toward the WBG in Peru; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Peru; and 4) their perceptions of the WBG’s future role in Peru.